An exploratory examination of At-Risk/Problematic Internet Use and disordered eating in adults. (January 2017) - Ivezaj, Valentina; Potenza, Marc N.; Grilo, Carlos M.; White, Marney A.
Abstract: Purpose: At-Risk/Problematic Internet Use (ARPIU) has been associated with impairment in multiple domains including psychopathology. The present study examined the relationship between ARPIU and disordered eating in a large community sample. Methods: Participants (n = 1000) completed an online survey about health behaviors. Two thresholds of ARPIU and disordered eating each were examined. Results: The ARPIU and Sub-ED (subthreshold eating disorders) groups reported greater depressive symptoms and poorer self-control than the Control group; the Sub-ED group reported greater impulsivity than the Control group. The ARPIU and Sub-ED groups significantly differed in key features related to each condition. Finally, the co-occurrence of ARPIU and Sub-ED was associated with greater depression. In the second set of analyses based on more stringent thresholds, the Problematic Internet Use (PIU) and ED groups differed on all measures compared to the Control group. The PIU and ED groups also differed on key features related to each condition, but did not differ on measures of impulsivity or self-control. The co-occurrence of PIU and ED was associated with greater depressive symptoms than either PIU or ED independently. Conclusions: ARPIU and Sub-ED share links to depression and poor self-control and these may represent possible therapeutic targets across Internet-use and disordered-eating behaviors. Co-occurring PIU and ED at either lenient or stringent thresholds is associated with greater depression. Future studies should examine the temporal nature of these associations and the extent to which targeting depression, Internet use, or disordered eating may lead to improvements across domains. Highlights: Examined At-Risk/Problematic Internet Use (ARPIU/PIU) and eating disorders (EDs) ARPIU/PIU and subthreshold/full ED groups reported greater pathology than controls. ARPIU/PIU and Sub-ED/ED share links to depression and poor self-control. Co-occurrence of ARPIU and subthreshold ED was associated with greater depression. Co-occurrence of PIU and ED was associated with greater depression.